Determination of forest priority levels for wild boar by analysis of habitat suitability and landscape connectivity - Tang, Tao; Li, Jiping; Velázquez, Javier (Frontiers in Ecology and Evolution, 2023)
The reduction and fragmentation of forests due to human activities are two primary factors that have led to forest biodiversity losses. The lack of forest continuation may prevent organisms from escaping areas that are no longer habitable due to altered environmental conditions and the reduction in size of habitat regions.Therefore, protecting and promoting forest connectivity has become one of the important objectives of forest management. The forests were regarded as independent elements, and the connectivity of the forest itself was directly evaluated in previous studies. However, this approach ignores the maintenance of forest connectivity, while requiring the participation of other landscape elements. In this study, we indirectly determine the forest priority by evaluating the landscape priority by integrating analysis with the habitat suitability (HS) model, MSPA and PC k BC and k dPC index.We studied the wild boar (Sus scrofa) habitats in and around Hupingshan and Houhe National Nature Reserves to illustrate the indirect evaluation method of forest priority.The results showed that forests with high priority, medium priority, low priority, and non-priority comprised 596, 64, 58 and 105 km 2 , respectively, accounting for the 41.2, 2.7, 3.0, and 11.9% of the total forest area. Our research revealed that evaluating the forest priority by analysing the landscape priority was an effective method for forest priority identification, and this strategy can be used to other regions or species for the goal of identifying the forest priority for biodiversity conservation.